Expressão de clpB em resposta a estresse causado por choque térmico e antibióticos em Acinetobacter baumannii - Lazaretti, Waleska Yana (2018)
Acinetobacter baumannii (A. baumannii) is an important opportunistic, Gram-negative pathogen responsible for severe nosocomial infections such as pneumonia, septicemia, urinary tract infections and meningitis. Strains of A. baumannii have been identified in an endemic and epidemic manner in hospitals, being verified the occurrence of multiresistant strains in these environments, with important ability to adapt to selective changes and environmental pressures. Furthermore, multidrug resistance to antibiotics has been continuously studied because it is a global public health problem, resulting in failure of therapy, prolongation of hospitalization, increase of mortality and morbidity rates, and increase in the financial costs of treatment. This pathogen has varied strategies involved with antimicrobial resistance, but it is known that the bacteria are able to respond to unfavorable conditions in the medium through the rapid expression of heat shock proteins (HSP) and also appear to be involved with the stress response caused by the presence of antibiotics. Among the HSPs is ClpB, an ATP-dependent molecular chaperone belonging to the HSP100 family that is associated with several cellular activities, with the remarkable ability to rescue proteins damaged by stress. The objective of this work was to investigate the role of the clpB gene responsible for the coding of a heat shock protein through qPCR in response to stress generated by thermal shock and antibiotics in cells of a multidrug resistant strain of A. baumannii (RS4). Tests performed included analysis of the structure of the clpB gene with bioinformatics tools and analysis of the expression of the same gene by qRT-PCR in response to exposure to heat shock and subinhibitory concentrations of the following antibiotics: ampicillin (30 g mL-1 ), amoxicillin + sulbactam (12 g mL-1), cefepime (30 g mL-1), sulfamethoxazole + trimethoprim (120/8 g mL-1) and meropenem (18 g mL-1).The analysis of the qPCR results showed a transient increase in the induction of the clpB gene in the different treatments used in this study and repression of mRNA-clpB in the presence of cefepime. In addition, in the presence of ampicillin and amoxicillin associated with sulbactam the increase in mRNA-clpB synthesis was around 1.4 times higher after 20 min of incubation with the antibiotics than in the complete absence of the antibiotics. Surprisingly, in the presence of meropenen the induction of mRNA-clpB expression was more than 30-fold higher after 10 minutes of incubation with the antibiotic and more than 8-fold higher in the presence of sulfamethoxazole associated with trimetropin. These data suggest that A. baumannii through thermal stress and antibiotic exposure, adjusts transcription levels of gene clpB allowing the bacterium to survive unfavorable conditions of the medium. Consequently, it can be stated that the protein encoded by the clpB gene is an important virulence factor in response to antibiotics in this pathogen.